Composite negative electrode sheet and method for manufacturing the same

CN117334838BActive Publication Date: 2026-10-27SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311399756.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2026-10-27
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

为了避免该现象,通常采用降低极片的压实密度来提高锂离子电池的动力学性能,但会损失能量密度;或者是改变负极粘结剂,改善析锂的同时会引发电池循环膨胀等问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004514866440000101
    Figure BDA0004514866440000101
  • Figure BDA0004514866440000111
    Figure BDA0004514866440000111
  • Figure BDA0004514866440000121
    Figure BDA0004514866440000121
Patent Text Reader

Abstract

The application relates to a composite negative electrode sheet and a preparation method thereof. The composite negative electrode sheet comprises a current collector and a negative electrode coating, wherein the negative electrode coating comprises a first negative electrode coating and a second negative electrode coating, the first negative electrode coating is coated on the surface of the current collector, and the second negative electrode coating is coated on the side of the first negative electrode coating away from the current collector. The composite negative electrode sheet satisfies the relationship: 0.01 <= alpha1 <= 0.1, 0.005 <= alpha2 <= 0.05 and alpha1 > alpha2, so that the composite negative electrode sheet has good rapid charging capacity and is not prone to lithium precipitation during the charging process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a composite negative electrode sheet and its preparation method. Background Technology

[0002] With the increasing depletion of fossil fuels and the arrival of the new energy era, lithium-ion batteries, as a mainstay of new energy sources, are widely used in all aspects of life. These include mobile phones, laptops, electric bicycles, electric vehicles, and even various energy storage devices. Consequently, consumers are increasingly demanding higher performance from lithium-ion batteries.

[0003] As a typical rechargeable battery, lithium-ion batteries involve lithium ions moving from the positive electrode to the negative electrode and embedding themselves in the negative electrode plate during charging. During discharging, lithium ions move from the inside of the negative electrode plate to the surface of the negative electrode and then detach and move towards the positive electrode. Therefore, the negative electrode plate, as an important component of the battery, typically determines the charging capacity, cycle performance, and safety performance of the lithium-ion battery.

[0004] The most common safety issue during fast charging of lithium-ion batteries is lithium plating. To avoid this, the compaction density of the electrodes is usually reduced to improve the kinetic performance of the lithium-ion battery, but this results in a loss of energy density; alternatively, the negative electrode binder is changed to improve lithium plating, but this can lead to problems such as battery cycle expansion.

[0005] Therefore, developing a novel battery anode is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] Based on this, the first aspect of this application is to provide a composite negative electrode sheet comprising two negative electrode coatings. By regulating the synergistic and fitting relationship between the porosity of each negative electrode coating, the particle size of the negative electrode active material and the bifacial density of the negative electrode coating, as well as the relationship between the two negative electrode coatings, it is helpful to improve the charging capability of lithium-ion batteries and improve the lithium plating phenomenon on the negative electrode surface.

[0007] A composite negative electrode sheet, characterized in that it comprises:

[0008] Current collector, and

[0009] A negative electrode coating, comprising a first negative electrode coating and a second negative electrode coating;

[0010] The first negative electrode coating is applied to the surface of the current collector, and the second negative electrode coating is applied to the side of the first negative electrode coating away from the current collector;

[0011] The negative electrode coating contains a negative electrode active material, which is graphite;

[0012] The first negative electrode coating satisfies: 0.01 ≤ α1 ≤ 0.1;

[0013] The second negative electrode coating satisfies: 0.005 ≤ α2 ≤ 0.05;

[0014] The composite negative electrode sheet satisfies the following relationship: α1>α2,

[0015] Among them, α1=ε1*δ1 / ρ1; α2=ε2*δ2 / ρ2;

[0016] ε1 and ε2 are the porosities of the first and second negative electrode coatings, respectively.

[0017] δ1 and δ2 are the particle sizes D of the negative electrode active material in the first and second negative electrode coatings, respectively. 50 Value, in μm

[0018] ρ1 and ρ2 are the bifacial areal densities of the first and second negative electrode coatings, respectively, in g / m³. 2 .

[0019] In some of these implementations, ε1 > ε2.

[0020] In some embodiments, the porosity ε1 of the first negative electrode coating is 15% to 60%; the porosity ε2 of the second negative electrode coating is 15% to 60%.

[0021] In some embodiments, the porosity ε1 of the first negative electrode coating is 20% to 50%; and the porosity ε2 of the second negative electrode coating is 15% to 60%.

[0022] In some embodiments, the porosity ε1 of the first negative electrode coating is 25% to 45%; the porosity ε2 of the second negative electrode coating is 25% to 45%.

[0023] In some of these implementations, δ1 < δ2.

[0024] In some embodiments, the particle size D of the negative electrode active material in the first negative electrode coating 50 The value δ1 is 5μm to 25μm; the particle size D of the negative electrode active material in the second negative electrode coating 50 The value δ2 ranges from 5 μm to 25 μm.

[0025] In some embodiments, the particle size D of the negative electrode active material in the first negative electrode coating 50 The value δ1 is 5μm to 20μm; the particle size D of the negative electrode active material in the second negative electrode coating 50 The value δ2 ranges from 5 μm to 20 μm.

[0026] In some embodiments, the bifacial areal density ρ1 of the first negative electrode coating is 80 g / m².2 ~300g / m 2 The double-sided areal density ρ2 of the second negative electrode coating is 80 g / m³. 2 ~300g / m 2 .

[0027] In some of these implementations, the ratio of α1 to α2 is (2-3):1.

[0028] In some of these embodiments, graphite includes at least one of natural graphite and artificial graphite.

[0029] The second aspect of this application also provides a method for preparing the composite negative electrode sheet of the first aspect of this application, comprising the following steps:

[0030] The first negative electrode slurry is coated onto the surface of the current collector and dried to obtain the negative electrode sheet; and

[0031] The second negative electrode slurry is coated on the surface of the negative electrode sheet away from the current collector, and after drying, a composite negative electrode sheet is obtained.

[0032] The first negative electrode coating satisfies: 0.01 ≤ α1 ≤ 0.1;

[0033] The second negative electrode coating satisfies: 0.005 ≤ α2 ≤ 0.05;

[0034] The composite negative electrode sheet satisfies the following relationship: α1>α2,

[0035] α1=ε1*δ1 / ρ1; α2=ε2*δ2 / ρ2;

[0036] ε1 and ε2 are the porosities of the first and second negative electrode coatings, respectively.

[0037] δ1 and δ2 are the particle sizes D of the negative electrode active material in the first and second negative electrode coatings, respectively. 50 Value, in μm

[0038] ρ1 and ρ2 are the bifacial areal densities of the first and second negative electrode coatings, respectively, in g / m³. 2 .

[0039] The composite negative electrode sheet of this application comprises a two-layer structure of a first negative electrode coating and a second negative electrode coating based on the current collector. The porosity ε1 and ε2 of each negative electrode coating, the particle size δ1 and δ2 of the negative electrode active material, and the relationship between the two-sided areal densities ρ1 and ρ2 of the negative electrode coating are reasonably controlled. Based on the range of α1 in 0.01 to 0.1 and α2 in 0.005 to 0.05, the control is adjusted so that α1 > α2, where α1 = ε1*δ1 / ρ1 and α2 = ε2*δ2 / ρ2. Under this condition, the lithium-ion battery has a smaller DC internal resistance and better fast charging capability. At the same time, lithium plating is less likely to occur on the surface of the composite negative electrode sheet during charging, and the lithium-ion battery has good cycle performance. Detailed Implementation

[0040] Reference will now be made to detailed embodiments of this application, one or more of which are described below. Each example is provided for explanation and not for limitation of this application. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.

[0041] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.

[0042] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0043] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0044] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0045] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0046] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0047] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0048] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0049] This application relates to a composite negative electrode sheet, comprising a current collector and a negative electrode coating, wherein the negative electrode coating includes a first negative electrode coating and a second negative electrode coating, the first negative electrode coating being coated on the surface of the current collector, and the second negative electrode coating being coated on the side of the first negative electrode coating away from the current collector. The negative electrode coating contains a negative electrode active material, including graphite.

[0050] The first negative electrode coating satisfies the following relationship: 0.01 ≤ α1 ≤ 0.1, and the second negative electrode coating satisfies the following relationship: 0.005 ≤ α2 ≤ 0.05; furthermore, the first and second negative electrode coatings satisfy the following relationship: α1 > α2. Here, α1 = ε1 * δ1 / ρ1, α2 = ε2 * δ2 / ρ2. Where ε1 and ε2 are the porosities of the first and second negative electrode coatings, respectively, and δ1 and δ2 are the particle sizes D of the negative electrode active material in the first and second negative electrode coatings, respectively. 50 The values ​​are in μm, and ρ1 and ρ2 are the bifacial areal densities of the first and second negative electrode coatings, respectively, in g / m². 2 .

[0051] When α1 is 0.01–0.1 and α2 is 0.005–0.05, lithium-ion batteries exhibit low DC internal resistance and good fast-charging capability, while also demonstrating good kinetic performance during charging and being less prone to lithium plating. Furthermore, when α1 > α2, the composite anode coating shows even better performance.

[0052] Wherein, α1 satisfies 0.01 to 0.1; including but not limited to 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc.

[0053] α2 satisfies 0.005 to 0.05; including but not limited to 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, etc.

[0054] Preferably, the ratio of α1 to α2 is (2-3):1.

[0055] In some of these embodiments, graphite includes at least one of natural graphite and artificial graphite.

[0056] In some embodiments, the porosities ε1 and ε2 of the first negative electrode coating and the second negative electrode coating are both 15% to 60%, including but not limited to 15%, 20%, 25%, 30%, 40%, 50%, 60%, etc.

[0057] At this point, the negative electrode exhibits good kinetic performance. As the porosity gradually increases, more pathways are available for lithium ions in the negative electrode, leading to a gradual increase in the conduction speed of lithium ions within the negative electrode. Therefore, during fast charging, lithium ions are transported more quickly and more easily into the negative electrode, effectively reducing the probability of lithium plating and improving battery safety and cycle performance. In liquid batteries, increased porosity also improves the wettability of the negative electrode in the electrolyte, further increasing the conduction speed of lithium ions; however, it also leads to increased interfacial reactions, thereby reducing the reversible capacity of the negative electrode, resulting in significant energy density loss and affecting the battery's cycle performance.

[0058] In some embodiments, the particle size D of the negative electrode active material in the first negative electrode coating and the second negative electrode coating is... 50The values ​​δ1 and δ2 are both 5μm to 25μm, including but not limited to 5μm, 8μm, 10μm, 15μm, 20μm, and 25μm. Under otherwise constant conditions, smaller particle size of the negative electrode active material helps reduce the transport resistance of lithium ions in the battery's negative electrode, thereby improving the kinetic performance of the negative electrode and thus enhancing the battery's fast-charging capability. However, smaller particle size leads to increased interfacial reactions, hindering lithium ion transport efficiency, causing a loss of battery energy density, and consequently affecting the battery's cycle performance.

[0059] Preferably, δ1 < δ2, meaning that the particle size of the negative electrode active material in the first negative electrode coating is smaller than that in the second negative electrode coating. This helps to further reduce the transport resistance of the negative electrode active material in the first negative electrode coating, thereby reducing the difference in lithium ion transport resistance between the first negative electrode coating and the second negative electrode coating, and improving the overall ion conduction efficiency of the composite negative electrode sheet.

[0060] In some embodiments, the bifacial areal densities ρ1 and ρ2 of both the first negative electrode coating and the second negative electrode coating are 80 g / m². 2 ~300g / m 2 including but not limited to 80g / m 2 100g / m 2 120g / m 2 150g / m 2 200g / m 2 300g / m 2 wait.

[0061] Under otherwise constant conditions, increasing the bifacial areal density of the negative electrode coating increases the resistance to lithium-ion transport, which is beneficial for improving battery energy density. However, it also leads to a decrease in porosity, which is detrimental to improving the fast-charging capability of lithium-ion batteries and can also result in poorer cycle performance. Conversely, decreasing the bifacial areal density of the negative electrode coating reduces the resistance to lithium-ion transport, which is beneficial for improving the kinetic performance of the negative electrode sheet, but it can severely impair battery energy density.

[0062] The composite negative electrode sheet of this application achieves this by rationally controlling the relationship between the porosity of the first negative electrode coating and the particle size and areal density of the negative electrode active material in the second negative electrode coating. This ensures that the first negative electrode coating satisfies 0.01≤α1≤0.1, the second negative electrode coating satisfies 0.005≤α2≤0.05, and α1>α2. Where α1=ε1*δ1 / ρ1, α2=ε2*δ2 / ρ2, the negative electrode sheet exhibits good fast charging capability and is less prone to lithium plating during charging, resulting in high battery cycle performance.

[0063] The second aspect of this application also provides a method for preparing the negative electrode sheet of the first aspect of this application, comprising the following steps:

[0064] The first negative electrode slurry is coated onto the surface of the current collector and dried to obtain the negative electrode sheet; and

[0065] The second negative electrode slurry is coated onto the surface of the negative electrode sheet away from the current collector, and after drying, a composite negative electrode sheet is obtained. The first negative electrode sheet satisfies the following relationship: 0.01≤α1≤0.1, α1=ε1*δ1 / ρ1; the second negative electrode coating satisfies the following relationship: 0.005≤α2≤0.05, α2=ε2*δ2 / ρ2; ε1 and ε2 are the porosities of the first and second negative electrode coatings, respectively, and δ1 and δ2 are the particle sizes D of the negative electrode active material in the first and second negative electrode coatings, respectively. 50 The values ​​are in μm, and ρ1 and ρ2 are the bifacial areal densities of the first and second negative electrode coatings, respectively, in g / m². 2 .

[0066] It is understood that this application does not specifically limit the negative electrode current collector. As long as it is conductive and does not cause chemical changes in the battery, it is acceptable, provided it does not deviate from the inventive concept of this application. For example, the negative electrode current collector can be made of aluminum, copper, nickel, zinc, or zinc alloys, etc.; the shape of the negative electrode current collector can be foil, plate, or mesh, etc.

[0067] In some embodiments, the first negative electrode slurry includes a first negative electrode active material, a first negative electrode binder, and a first negative electrode conductive agent; the second negative electrode slurry includes a second negative electrode active material, a second negative electrode binder, and a second negative electrode conductive agent.

[0068] In some embodiments, the negative electrode active material includes graphite, that is, both the first and second negative electrode active materials are graphite. Graphite includes at least one of natural graphite, artificial graphite, and compound graphite.

[0069] Both the first negative electrode binder and the second negative electrode binder are polymeric compounds used to adhere the negative electrode active material to the negative electrode current collector. The first negative electrode binder and the second negative electrode binder may be the same or different.

[0070] It is understood that this application does not specifically limit the types of the first and second negative electrode binders. Any binder capable of bonding and maintaining the negative electrode active material, enhancing the contact between the negative electrode active material and the negative electrode conductive agent, and between the negative electrode active material and the negative electrode current collector, thereby stabilizing the structure of the negative electrode sheet, without departing from the inventive concept of this application, is within the scope of protection of this application. Exemplarily, it includes thermoplastic resins or thermosetting resins. Examples include polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc.

[0071] Both the first and second negative electrode conductive agents are used to further improve the conductivity of the negative electrode active material layer. The first and second negative electrode conductive agents can be the same or different.

[0072] It is understood that this application does not specifically limit the types of the first and second negative electrode conductive agents. Exemplary examples include at least one of carbon-based materials, powdered nickel or other metal particles, or conductive polymers. Examples include natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, acetylene black, carbon nanotubes, carbon nanofibers, polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene)polysulfonated styrene, etc.

[0073] In some embodiments, after the drying step, the method for preparing the composite negative electrode sheet of this application further includes a rolling step.

[0074] It is understood that this application does not impose special limitations on the roller diameter, roller pressure, roller temperature, and other related process parameters during rolling. Any conventional adjustments made to parameters such as the thickness of the composite negative electrode sheet and the porosity of the first and / or second negative electrode coating, without departing from the inventive concept of this application, should be considered within the scope of protection of this application. This application also does not impose special requirements on the drying process. Any known drying process can be used in this application without departing from the inventive concept. These are merely illustrative examples and not intended to limit the scope of protection. The drying process can be carried out by baking, hot rolling, etc.

[0075] During the preparation process, the porosity and double-sided surface density of the first and / or second negative electrode coatings are controlled by adjusting the mass of the first and / or second negative electrode slurry, the surface area of ​​the first and / or second negative electrode slurry coated on the current collector, the coating thickness of the first and / or second negative electrode slurry, the drying temperature and time, and the rolling pressure.

[0076] The embodiments of the present invention will now be described in more detail through examples. However, the embodiments of the present invention are not limited to these examples.

[0077] Example 1

[0078] (1) Preparation of composite negative electrode sheet

[0079] Artificial graphite, (CMC+SBR), and acetylene black were weighed in a mass ratio of 95:3:2, wherein the particle size D of the graphite was... 50 With a value of 5μm, the aforementioned material was placed in a vacuum mixer and stirred, while deionized water was added as a solvent. After stirring evenly, a uniformly mixed first negative electrode slurry was obtained.

[0080] Artificial graphite, (CMC+SBR), and acetylene black were weighed in a mass ratio of 95:3:2, wherein the particle size D of the graphite was... 50 With a value of 10μm, the aforementioned material was placed in a vacuum mixer and stirred while adding deionized water as a solvent. After stirring evenly, a uniformly mixed second negative electrode slurry was obtained.

[0081] The first negative electrode slurry is evenly coated on both surfaces of the copper foil. After coating, the electrode is transferred to an oven for drying. The temperature in the oven is 140℃ and the drying time is 600 seconds to obtain the first negative electrode.

[0082] The second negative electrode slurry is uniformly coated on the surface of the first negative electrode coating away from the current collector. After coating, it is transferred to an oven for drying. The temperature in the oven is 140°C and the drying time is 600 seconds to obtain the second negative electrode sheet.

[0083] The second negative electrode sheet is rolled and then slit to obtain a composite negative electrode sheet.

[0084] (2) Preparation of lithium-ion batteries

[0085] Weigh out the positive electrode active material NCM333, conductive agent acetylene black, and binder PTFE in a mass ratio of 95:3:2, dissolve them in the solvent NMP, stir evenly, coat them on aluminum foil, dry, roll, and cut to obtain the positive electrode sheet.

[0086] A lithium-ion battery is obtained by stacking positive electrode sheets, composite negative electrode sheets, and separators, placing them in an aluminum-plastic film, and then injecting liquefaction.

[0087] (3) Detect the porosity of the first and second negative electrode coatings.

[0088] The porosities ε1 and ε2 of the first and second negative electrode coatings in the composite negative electrode sheet were obtained by the mass difference method. The first and composite negative electrode sheets were cut into circular sheets with a radius r of 0.95 cm using an electrode sheet punching machine. The mass of the cut first negative electrode sheet was recorded as m1, and the mass of the composite negative electrode sheet was recorded as m2, using a balance with an accuracy of 0.00001 g. The first negative electrode sheet was soaked in hexadecane for 1 hour (completely submerged). The electrode sheet was then removed with tweezers and blotted dry with filter paper until a constant weight was achieved. Its mass was then recorded as m0.

[0089] The composite negative electrode sheet was analyzed by scanning electron microscopy (SEM) using ion-polished cross-sectional morphology (referencing JY / T010-1996) (measurements were taken at least 5 locations, and the average value was used). The thicknesses of the current collector, the first negative electrode coating, and the second negative electrode coating were measured as L0, L1, and L2, respectively. Then, the volume of active material in the first negative electrode coating on the composite negative electrode sheet was calculated as V1 = π*r. 2 *(L1-L0); The volume of active material in the second negative electrode coating is V2=π*r 2 *(L2-L1). Substitute the experimental data into the formula to calculate: ε1=(m1-m0) / (V1*ρ0)*100%, ε2=(m2-m1) / (V2*ρ0)*100%. Where ρ0 is the density of hexadecane, 0.7734 g / cm³. 3 The porosity ε1 of the first negative electrode coating and the porosity ε2 of the second negative electrode coating are obtained.

[0090] Examples 2-16 and Comparative Examples 1-5 used the same method as Example 1, but selected artificial graphite particles of different sizes. During the preparation of the composite negative electrode sheet, the process parameters for coating, drying, and rolling were adjusted to achieve the desired porosity of the first and second negative electrode coatings and the particle size D of the negative electrode active material in the first and second negative electrode coatings. 50 The values ​​and the areal densities of the first and second negative electrode coatings are as shown in Table 1. Different composite negative electrode sheets were prepared, and the data are compiled as shown in Table 1. The values ​​of α1, α2 and α1:α2 were calculated and recorded in Table 1.

[0091] Wherein, the double-sided surface density of the first negative electrode coating = weight of the first negative electrode slurry / surface area of ​​both sides of the first negative electrode coating; the double-sided surface density of the second negative electrode coating = weight of the second negative electrode slurry / surface area of ​​both sides of the second negative electrode coating.

[0092] Table 1

[0093]

[0094]

[0095] Experimental Example

[0096] (1) Room temperature 3C rate performance test:

[0097] The lithium-ion batteries provided in the examples and comparative examples were charged at 1C to the termination voltage at room temperature, with a cutoff current of 0.05C. After standing for 30 minutes, they were discharged at 1C and 3C to the termination voltage, respectively. The discharge capacity was recorded. The room temperature 3C rate discharge performance was obtained by comparing the 3C discharge capacity with the 1C discharge capacity.

[0098] (2) Capacity retention test after 500 cycles at room temperature:

[0099] At room temperature, the lithium-ion batteries provided in the examples and comparative examples were charged to the termination voltage at 1C or a specified current, with a cutoff current of 0.05C, and left to stand for 30 minutes; then discharged at 1C to the final discharge voltage, and the discharge capacity was recorded, followed by a 30-minute stand; the charge-discharge cycle was repeated for 500 cls and the data was recorded.

[0100] (3) Lithium plating test:

[0101] The lithium-ion battery used as the test object was cycled at 25°C for 1000cls. The lithium-ion batteries provided in the examples and comparative examples were charged to 100% SOC at a 1C rate. Then, the negative electrode of the lithium-ion battery was disassembled and the lithium deposition on the surface of the negative electrode was observed and recorded.

[0102] The lithium plating situation is divided into three categories: slight lithium plating, moderate lithium plating, and severe lithium plating. Slight lithium plating means that the area of ​​the lithium plating region on the surface of the negative electrode is less than or equal to 10%; moderate lithium plating means that the area of ​​the lithium plating region on the surface of the negative electrode is 10% to 50%; and severe lithium plating means that the area of ​​the lithium plating region on the surface of the negative electrode is greater than 50%.

[0103] The data from Examples 1-16 and Comparative Examples 1-5 are compiled as shown in Table 2.

[0104] Table 2

[0105]

[0106] Based on the data in Tables 1 and 2, it can be seen that this application uses multilayer electrodes, and has the best performance when both the first negative electrode coating and the second negative electrode coating meet the conditions defined in this application.

[0107] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0108] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A composite negative electrode sheet, characterized in that, include: Current collector, and A negative electrode coating, wherein the negative electrode coating includes a first negative electrode coating and a second negative electrode coating; The first negative electrode coating is applied to the surface of the current collector, and the second negative electrode coating is applied to the side of the first negative electrode coating away from the current collector; The negative electrode coating contains a negative electrode active material, which is graphite. The first negative electrode coating satisfies: 0.01 ≤ α1 ≤ 0.1; The second negative electrode coating satisfies: 0.005 ≤ α2 ≤ 0.05; The ratio of α1 to α2 is (2~3):1; Among them, α1=ε1*δ1 / ρ1; α2=ε2*δ2 / ρ2; ε1 and ε2 are the porosities of the first negative electrode coating and the second negative electrode coating, respectively, and ε1>ε2; δ1 and δ2 are the particle sizes D of the negative electrode active material in the first and second negative electrode coatings, respectively. 50 Values, in μm, where δ1 < δ2; ρ1 and ρ2 are the bifacial areal densities of the first and second negative electrode coatings, respectively, in g / m³. 2 ; The porosity ε1 of the first negative electrode coating is 20%~60%. The porosity ε2 of the second negative electrode coating is 15% to 50%. The particle size D of the negative electrode active material in the first negative electrode coating 50 Value δ1 ranges from 5 μm to 24 μm; The particle size D of the negative electrode active material in the second negative electrode coating 50 The value δ2 is 10 μm to 25 μm; The double-sided areal density ρ1 of the first negative electrode coating is 80 g / m². 2 ~300 g / m 2 ; The double-sided areal density ρ2 of the second negative electrode coating is 80 g / m². 2 ~300 g / m 2 .

2. The negative electrode sheet according to claim 1, characterized in that, The graphite includes at least one of natural graphite, artificial graphite, and compound graphite.

3. A method for preparing the composite negative electrode sheet according to any one of claims 1 to 2, characterized in that, Includes the following steps: The first negative electrode slurry is coated onto the surface of the current collector and dried to obtain the negative electrode sheet; and The second negative electrode slurry is coated on the surface of the negative electrode sheet away from the current collector, and after drying, a composite negative electrode sheet is obtained. The first negative electrode coating satisfies: 0.01 ≤ α1 ≤ 0.1; The second negative electrode coating satisfies: 0.005 ≤ α2 ≤ 0.05; The ratio of α1 to α2 is (2~3):1; α1=ε1*δ1 / ρ1; α2=ε2*δ2 / ρ2; ε1 and ε2 are the porosities of the first negative electrode coating and the second negative electrode coating, respectively, and ε1>ε2; δ1 and δ2 are the particle sizes D of the negative electrode active material in the first and second negative electrode coatings, respectively. 50 Values, in μm, where δ1 < δ2; ρ1 and ρ2 are the bifacial areal densities of the first and second negative electrode coatings, respectively, in g / m³. 2 ; The porosity ε1 of the first negative electrode coating is 20%~60%. The porosity ε2 of the second negative electrode coating is 15% to 50%. The particle size D of the negative electrode active material in the first negative electrode coating 50 Value δ1 ranges from 5 μm to 24 μm; The particle size D of the negative electrode active material in the second negative electrode coating 50 The value δ2 is 10 μm to 25 μm; The double-sided areal density ρ1 of the first negative electrode coating is 80 g / m². 2 ~300 g / m 2 ; The double-sided areal density ρ2 of the second negative electrode coating is 80 g / m². 2 ~300 g / m 2 .

Citation Information

Patent Citations

  • Negative plate and secondary battery

    CN114079032A

  • Negative pole piece, electrochemical device and electronic equipment

    CN114649500A